2017
DOI: 10.1002/1873-3468.12880
|View full text |Cite
|
Sign up to set email alerts
|

N‐terminal S‐acylation facilitates tonoplast targeting of the calcium sensor CBL6

Abstract: Protein S-acylation is important for many biological processes. It confers proteins with the ability to attach to the plasma membrane and the membranes confining the ER and Golgi compartments. Yet, the contribution of S-acylation to regulating and targeting lysosomal/vacuolar proteins remains largely enigmatic. Here, we report that vacuolar targeting of the calcium sensor calcineurin B-like protein 6 (CBL6) from Arabidopsis thaliana is brought about by S-acylation of N-terminal cysteine residues. Our results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 45 publications
(88 reference statements)
4
14
0
Order By: Relevance
“…Especially, CIPK16 and CIPK25 increased 27.33 and 17.02 times in coldtreated ScCBL6-OXP, indicating their potential interaction with ScCBL6. However, for the untreated comparison of WT and ScCBL6-OXP, no CIPK was significantly up-regulated, this result well correlated with the temperature dependence of CBL6/CIPK complex formation documented in Zhang et al [25]. In total, for cold stress response conferred by ScCBL6, many genes like GULLO2 and PCAP2 were potential targets to improve cold tolerance in other crop plant, however, for the lack of transformation system for Stipa capillacea, their underlying functional mechanism and pros and cons plasticity in other plant need more experimental investigation.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Especially, CIPK16 and CIPK25 increased 27.33 and 17.02 times in coldtreated ScCBL6-OXP, indicating their potential interaction with ScCBL6. However, for the untreated comparison of WT and ScCBL6-OXP, no CIPK was significantly up-regulated, this result well correlated with the temperature dependence of CBL6/CIPK complex formation documented in Zhang et al [25]. In total, for cold stress response conferred by ScCBL6, many genes like GULLO2 and PCAP2 were potential targets to improve cold tolerance in other crop plant, however, for the lack of transformation system for Stipa capillacea, their underlying functional mechanism and pros and cons plasticity in other plant need more experimental investigation.…”
Section: Discussionsupporting
confidence: 84%
“…As documented in Zhang et al [25] and results of subcellular location of ScCBL6 (Fig. 1C), we inferred that ScCBL6 mediated cold tolerance by targeting of organelle located proteins.…”
Section: Prospective Cold Tolerance Mechanism Mediated By Sccbl6supporting
confidence: 84%
See 1 more Smart Citation
“…In N. benthamiana, CNGC19 localized to the plasma membrane and overlays with PM-mCherry marker, but not with TP-mCherry ( Figure 3D). According to Nelson et al (2007) and Zhang et al (2017a), one of the clear features of vacuolar localization is the presence of transvacuolar strands and separation of tonoplast from neighboring cells, which we see in TP-mCherry (arrow, Supplemental Figure 7A). We found that CNGC19 does not overlay with any of these features using TP-mCherry (arrows in Figure 3D and Supplemental Figure 7A).…”
Section: Cngc19 Is a Plasma Membrane-localized Ca 21 -Permeable Channelmentioning
confidence: 69%
“…Localization studies have revealed that the Arabidopsis CBL proteins harboring a short N-terminal domain (CBL1, CBL4, CBL5 and CBL9) were localized at the plasma membrane due to myristoylation and palmitoylation. CBL proteins harboring an extended N-terminal domain (CBL2, CBL3 and CBL6) are localized at the tonoplast (D'Angelo et al, 2006;Cheong et al, 2007;Batistic et al, 2008;Batistic et al, 2010;Schlücking et al, 2013;Saito et al, 2018;Zhang et al, 2017). CBL7 and CBL8, both underwent evolutionary changes of their original N-terminal sequences, are localized in the cytoplasm and in the nucleus and, CBL10, having unique N-terminal region, can be detected in endosomal compartments, as well as at the tonoplast .…”
Section: Localization Of Cbl and Cipk Proteinsmentioning
confidence: 99%